Did Oligocene crustal thickening precede basin development in northern Thailand? A geochronological reassessment of Doi Inthanon and Doi Suthep - Gardiner, Nicholas; Roberts, N.; Morley, C.; Searle, M.; Whitehouse, M. (2016)
The Doi Inthanon and Doi Suthep metamorphic core complexes in northern Thailand are comprised of amphibolite-grade migmatitic gneisses mantled by lower-grade mylonites and metasedimentary sequences, thought to represent Cordilleran-style core complexes exhumed through the mobilization of a low-angle detachment fault. Previous studies have interpreted two metamorphic events (Late Triassic and Late Cretaceous), followed by ductile extension between the late Eocene and late Oligocene, a model which infers movement on the detachment at ca. 40. Ma, and which culminates in a rapid unroofing of the complexes in the early Miocene. The Chiang Mai Basin, the largest such Cenozoic Basin in the region, lies immediately to the east. Its development is related to the extension observed at Doi Inthanon and Doi Suthep, however it is not definitively dated, and models for its development have difficulty reconciling Miocene cooling ages with Eocene detachment movement. Here we present new in-situ LA-ICP-MS and SIMS U-Pb age data of zircon and monazite grains from gneiss and leucogranite samples taken from Doi Inthanon and Doi Suthep. Our new zircon data exhibit an older age range of 221-210. Ma, with younger ages of ca. 72. Ma, and 32-26. Ma. Our monazite data imply an older age cluster at 83-67. Ma, and a younger age cluster of 34-24. Ma. While our data support the view of Indosinian basement being reworked in the Cretaceous, they also indicate a late Eocene-Oligocene tectonothermal event, resulting in prograde metamorphism and anatexis. We suggest that this later event is related to localized transpressional thickening associated with sinistral movement on the Mae Ping Fault, coupled with thickening at the restraining bend of the Mae Yuan Fault to the immediate west of Doi Inthanon. Further, this upper Oligocene age limit from our zircon and monazite data would imply a younger Miocene constraint on movement of the detachment, which, when combined with the previously recorded Miocene cooling ages, has implications for a model for the onset of extension and subsequent development of the Chiang Mai Basin in the early mid-Miocene.